Development of Mg-doped hematite (α-Fe2O3)-based hydroelectric cell to generate green electricity. (26th October 2022) - Aarti; Gaur, Anurag; Shah, Jyoti; Kotnala, R. K.; Kumar, Dinesh
Abstract : The fabricated Mg-doped 'α-Fe2 O3 '-based HEC generates a short circuit current of ∼40 mA and power output of 36 mW. This is a promising device for producing green energy, and opens new avenues for alternative sources of green energy. Abstract : A revolutionary invention in the form of a hydroelectric cell (HEC) has opened a new arena in green energy production through water dissociation on the surface of defective metal oxides. In the present study, we have synthesized magnesium (Mg)-doped hematite (α-Fe2 O3 ) via solid state reaction route and studied the structural, electrical, and electrochemical properties. The X-ray diffraction study validates the pure phase formation of the pristine and Mg-doped 'α-Fe2 O3 '. The fabricated HEC generates a short circuit current of ∼40 mA and off-load power output of 36 mW. Further, the bulk resistance of the Mg-doped sample is lower (11.4 Ω) as compared to that of the pristine sample (37.41 Ω), which indicates that Mg doping improves the conductivity. The fabricated HEC is a promising device for producing green energy and opens new avenues for alternative sources of green energy.